2021
DOI: 10.3389/fcell.2021.714999
|View full text |Cite
|
Sign up to set email alerts
|

Is RAS the Link Between COVID-19 and Increased Stress in Head and Neck Cancer Patients?

Abstract: The COVID-19 pandemic emerged as a largely unexplained outbreak of pneumonia cases, in Wuhan City, China and rapidly spread across the world. By 11th March 2020, WHO declared it as a global pandemic. The resulting restrictions, to contain its spread, demanded a momentous change in the lifestyle of the general population as well as cancer patients. This augmented negative effects on the mental health of patients with head and neck cancer (HNC), who already battle with the stress of cancer diagnosis and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 151 publications
(161 reference statements)
0
4
0
Order By: Relevance
“…Intense work is in progress to develop a compound to target MAPK pathways to treat neurodegenerative and inflammatory diseases ( 77 ). Proliferation, apoptosis, and angiogenesis, the Renin-angiotensin signaling pathway (RAS) has been shown to play a role in tumorigenesis through complex interactions ( 78 ). Krishna Sriram et al reported that RAS has a great tendency to cause comorbidities and mortality and they proposed a model to predict effective drugs to target RAS ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intense work is in progress to develop a compound to target MAPK pathways to treat neurodegenerative and inflammatory diseases ( 77 ). Proliferation, apoptosis, and angiogenesis, the Renin-angiotensin signaling pathway (RAS) has been shown to play a role in tumorigenesis through complex interactions ( 78 ). Krishna Sriram et al reported that RAS has a great tendency to cause comorbidities and mortality and they proposed a model to predict effective drugs to target RAS ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…From a biologic standpoint, the mechanism of action of COVID-19 infection may provide a link between stress, cancer, and COVID-19 [ 26 ]. The causative agent for COVID-19, SARS-CoV2, enters the body through interaction with the angiotensin-converting enzyme 2 (ACE2) receptor.…”
Section: Psychosocial Assessment: Implications Of Delays In Carementioning
confidence: 99%
“…This receptor is involved in the Renin Angiotensin System (RAs) which is known to influence both cancer and stress. A recent review by Iftikhar et al suggests that COVID-19, stress, and cancer may interact mechanistically through RAS to facilitate progression of disease and stress [ 26 ].…”
Section: Psychosocial Assessment: Implications Of Delays In Carementioning
confidence: 99%
“…Thirty to Fifty percent of all cancer deaths could be prevented by adopting healthier lifestyles ( World Health Organization, 2022 ). Recent reviews have examined the direct and indirect role ( Iftikhar et al, 2021a , b ) that stress hormones play in the progression of HNC cancer. This current review explores the importance of stress as an upstream reason for the initiation and continuation of tobacco and alcohol use.…”
Section: Introductionmentioning
confidence: 99%